Analysis of The Influence of Digital Promotions, Perception of Ease, Transparency and Service Features Toward Public Intention to Use Digital Bank in Money Saving - Rezky Nurbakti; Lydia Gustina Putri; David Rindu Kurniawan; Loso Judijanto; Moh. Samsul Arifin (SEULANGA SYSTEM PUBLISHER, 2023)
The purpose of this study is to determine whether people's interest in saving in sharia digital banking applications is simultaneously positively and significantly influenced by views of convenience, service features, transparency, and advertising. Purposive sampling, a non-probability sampling technique, was utilized with a sample size of 100 people to select the research sample, which reflects the complete community that is aware of sharia digital banks but has not yet used the program. A survey or questionnaire is the research methodology used here. Multiple linear regression is used in this research's analysis model. Version 25 of SPSS is the tool in use. According to the findings of this study, all independent variables have a partial impact on the dependent variable. People's interest in saving via sharia digital banking applications is significantly and partially influenced by the Perception of Convenience variable. People's interest in saving in sharia digital banking applications is significantly and somewhat positively impacted by the service feature variable. The desire of individuals in saving in sharia digital banking applications is partially positively and significantly impacted by the transparency variable. The promotion variable partially influences peoples' desire to save in sharia digital banking applications in a positive and significant way. According to the study's findings, people's interest in saving in sharia digital banking applications is positively and significantly influenced by their perceptions of convenience, service characteristics, transparency, and promotion.